2009
DOI: 10.1074/jbc.m806891200
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated Sodium Channel Activity Promotes Cysteine Cathepsin-dependent Invasiveness and Colony Growth of Human Cancer Cells

Abstract: Voltage-gated sodium channels (Na V ) are functionally expressed in highly metastatic cancer cells derived from nonexcitable epithelial tissues (breast, prostate, lung, and cervix). MDA-MB-231 breast cancer cells express functional sodium channel complexes, consisting of Na V 1.5 and associated auxiliary ␤-subunits, that are responsible for a sustained inward sodium current at the membrane potential. Although these channels do not regulate cellular multiplication or migration, their inhibition by the specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
251
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(270 citation statements)
references
References 42 publications
(49 reference statements)
18
251
1
Order By: Relevance
“…They are known to be extracellularly active, even if the events leading to their extracellular secretion or activation are not well understood. Importantly, we confirm in this study that high amounts of immature forms of cathepsins are tonically released by cancer cells at much higher contents than active forms, which as already been reported (Roshy et al, 2003;Gillet et al, 2009). These cathepsins might be constitutively extruded from cellular compartments different from lysosomes, from which it is expected to only find active forms.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…They are known to be extracellularly active, even if the events leading to their extracellular secretion or activation are not well understood. Importantly, we confirm in this study that high amounts of immature forms of cathepsins are tonically released by cancer cells at much higher contents than active forms, which as already been reported (Roshy et al, 2003;Gillet et al, 2009). These cathepsins might be constitutively extruded from cellular compartments different from lysosomes, from which it is expected to only find active forms.…”
Section: Discussionsupporting
confidence: 91%
“…These channels have also been demonstrated to enhance the cysteine cathepsin-dependent invasiveness of breast cancer cells through the sodium influx (Gillet et al, 2009). P2X 7 R being non-specific cation-permeant channels, this raises the question of a possible involvement of internal sodium in the regulation of cathepsins activity/release and in the invasiveness of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have shown that voltage-gated sodium channels (Na V ) are abnormally expressed in cancer cells of epithelial origin and associated with cancer progression (Laniado et al, 1997;Roger et al, 2003Roger et al, , 2006Roger et al, , 2007Fraser et al, 2005;Diaz et al, 2007). In the highly invasive MDA-MB-231 breast cancer cell line, Na V 1.5 activity enhances extracellular matrix invasion by increasing the activity of acidic cysteine cathepsins B and S through an acidification of the pericellular microenvironment (Gillet et al, 2009). In this study, we investigated the potential pH regulators involved in the Na V -dependent invasiveness of MDA-MB-231 breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%